2004
DOI: 10.1083/jcb.200305142
|View full text |Cite
|
Sign up to set email alerts
|

Promyelocytic leukemia nuclear bodies associate with transcriptionally active genomic regions

Abstract: The promyelocytic leukemia (PML) protein is aggregated into nuclear bodies that are associated with diverse nuclear processes. Here, we report that the distance between a locus and its nearest PML body correlates with the transcriptional activity and gene density around the locus. Genes on the active X chromosome are more significantly associated with PML bodies than their silenced homologues on the inactive X chromosome. We also found that a histone-encoding gene cluster, which is transcribed only in S-phase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
181
2
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(202 citation statements)
references
References 57 publications
15
181
2
4
Order By: Relevance
“…Newly synthesized RNA is associated with the periphery of ND10, and many transcriptional regulators have been shown to biochemically interact with PML (49)(50)(51). However, other studies have found no association of nascent RNA, active transcription, or general transcription factors at ND10 (45,49,52). Kiesslich et al (53) confirmed that in nonsynchronized cells the majority of nascent RNA was not associated with ND10.…”
Section: Discussionsupporting
confidence: 59%
“…Newly synthesized RNA is associated with the periphery of ND10, and many transcriptional regulators have been shown to biochemically interact with PML (49)(50)(51). However, other studies have found no association of nascent RNA, active transcription, or general transcription factors at ND10 (45,49,52). Kiesslich et al (53) confirmed that in nonsynchronized cells the majority of nascent RNA was not associated with ND10.…”
Section: Discussionsupporting
confidence: 59%
“…Although RNA FISH and RNA interference (RNAi) experiments did not reveal a strict correlation of transcriptional activity and localization to PML-NBs, the majority of RNA transcript foci analyzed were positioned at the bodies. Furthermore, treatment of an APL cell line with all-trans retinoic acid resulted in the generation of PML-NBs and the concomitant localization of an active locus to the emergent structures (Wang et al 2004). It is therefore plausible that PML-NBs play a role in transcription, possibly as a reservoir of concentrated transcriptional regulators (Fig.…”
Section: Nuclear Bodiesmentioning
confidence: 99%
“…In support of a role in transcription, regulatory factors such as cyclic AMP response-binding protein (CBP) and retinoblastoma protein (pRB) have been shown to interact directly with PML (Ruggero et al 2000). A recent localization analysis of gene-dense domains in the human genome revealed that transcriptionally robust loci are associated with PML-NBs (Wang et al 2004). Although RNA FISH and RNA interference (RNAi) experiments did not reveal a strict correlation of transcriptional activity and localization to PML-NBs, the majority of RNA transcript foci analyzed were positioned at the bodies.…”
Section: Nuclear Bodiesmentioning
confidence: 99%
“…Since the known partners of HP1 in heterochromatin were absent from the bright HP1 focus, and HP1 and PML proteins have been shown to associate with transcriptionally active chromatin, [33][34][35] we searched for the presence of hallmarks of active chromatin at the bright focus. The distribution of the histone H3 acetylated on K9 and K18 (data not shown), the poly-acetylated histone H4 (Figure 7b), and the phosphorylated RNA polymerase II (Figure 7c) was examined, but none of them showed any specific signal co-localizing with the bright protein focus.…”
Section: Aberrant Nuclear Distribution Of Hp1a Hp1b and Hp1c Proteinmentioning
confidence: 99%